Innovation in the Era of Experience: The Changing Role of Users in Healthcare Innovation - Alexandre Trigo (Journal of Entrepreneurship, Management and Innovation)

(untitled)
This article provides an extensive literature review on the changing role of users in innovation, with a particular focus on the healthcare sector. Users have been specifically analyzed by many scholars worldwide due to their significant role as a source of innovation beyond the traditional assumption which considers customers as mere passive adopters of products and services. The increasing, but still scarce, number of studies on this topic has demonstrated the benefits of patient involvement and how a close and continuous relationship between patients and practitioners can lead to permanent cycles of improvements and innovation in healthcare outcomes. In addition to a user-centered approach, innovative patients are actively developing new solutions for their own treatments, likewise for other patients with similar diseases.